2010
DOI: 10.3324/haematol.2009.014274
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after relapse of acute lymphoblastic leukemia in adult patients included in four consecutive risk-adapted trials by the PETHEMA Study Group

Abstract: BackgroundAbout one half of adults with acute lymphoblastic leukemia are not cured of the disease and ultimately die. The objective of this study was to explore the factors influencing the outcome of adult patients with relapsed acute lymphoblastic leukemia. Design and MethodsWe analyzed the characteristics, the outcome and the prognostic factors for survival after first relapse in a series of 263 adult patients with acute lymphoblastic leukemia (excluding those with mature B-cell acute lymphoblastic leukemia)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
220
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 253 publications
(236 citation statements)
references
References 29 publications
11
220
1
4
Order By: Relevance
“…These results compare favorably with the other relatively large clofarabine study conducted in the adult setting which reported a CR rate of 15% [14]. Other studies evaluating classical ALL salvage regimens reported CR rates between 18 and 75% with less than 20% of long-term survivors [4][5][6]. The duration of CR in our patients was similar than in other studies performed in adults [15] but shorter than in the pediatric studies [13], probably due to the worse disease prognosis in the former.…”
supporting
confidence: 71%
See 2 more Smart Citations
“…These results compare favorably with the other relatively large clofarabine study conducted in the adult setting which reported a CR rate of 15% [14]. Other studies evaluating classical ALL salvage regimens reported CR rates between 18 and 75% with less than 20% of long-term survivors [4][5][6]. The duration of CR in our patients was similar than in other studies performed in adults [15] but shorter than in the pediatric studies [13], probably due to the worse disease prognosis in the former.…”
supporting
confidence: 71%
“…Most classical salvage regimens include several drugs used as first-line treatment with disappointing results. Noteworthy, the reported long-term survival for ALL patients beyond first relapse appears to be lower than 20% [3][4][5]. Commonly, these patients do not reach an allo-HCT due to chemoresistance to salvage regimen or to a very short lasting CR2, with relapse occurring before the identification of a suitable donor [6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to childhood leukemia, the clinical picture for adult T-ALL is even worse, with high relapse rates and long-term disease-free survival of about 40% (5)(6)(7). Altogether, these figures suggest that better and less toxic treatment strategies are urgently required to further improve the clinical management of childhood and adult T-ALL patients.…”
Section: Introductionmentioning
confidence: 99%
“…Adult patients with relapsed or refractory ALL have a poor prognosis and almost all patients will die from their disease [21][22][23][24][25][26][27][28]. While children are initially more responsive to traditional salvage chemotherapy approaches than adults, these remissions are often not sustained and relapsed ALL remains a leading cause of cancer deaths in children [29,30].…”
Section: Clinical Outcomes Of Cd19-car T-cell Therapymentioning
confidence: 99%